2012 IEEE International Geoscience and Remote Sensing Symposium 2012
DOI: 10.1109/igarss.2012.6351348
|View full text |Cite
|
Sign up to set email alerts
|

A multi-sensor (SMOS, AMSR-E and ASCAT) satellite-based soil moisture products inter-comparison

Abstract: Soil Moisture (SM), being one of the main variables within the system that controls the hydrological interactions among soil, vegetation and atmosphere, plays a key role in the water cycle. Satellite systems, both active and passive, have already demonstrated their capability to provide reliable SM measurements. The European Space Agency (ESA) Soil Moisture and Ocean Salinity (SMOS) mission, launched in November 2009, was the first specific SM satellite mission. In this work we assessed the capability of SMOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
8
0
3
Order By: Relevance
“…These studies showed that the variation range of the AMSR-E/NASA SM time series is significantly narrower than in-situ measurements and does not reflect the SM change due to rainfall events. The accuracy of this product was even lower for the Tibetan Plateau [11,13,14]. Under dry conditions, the NASA SM was overestimated and underestimated under wet conditions [12,15].…”
Section: Introductionmentioning
confidence: 89%
“…These studies showed that the variation range of the AMSR-E/NASA SM time series is significantly narrower than in-situ measurements and does not reflect the SM change due to rainfall events. The accuracy of this product was even lower for the Tibetan Plateau [11,13,14]. Under dry conditions, the NASA SM was overestimated and underestimated under wet conditions [12,15].…”
Section: Introductionmentioning
confidence: 89%
“…air temperature below 0). This is because SMOS is incapable of retrieving good quality soil moisture measurements under frozen weather (Lacava et al, 2012a;Al-Yaari et al, 2014;Wagner et al, 2014;Zhuo and Han, 2015). It has been further averaged into one catchmentscale dataset by applying the weighted average method.…”
Section: Study Area and Datasetsmentioning
confidence: 99%
“…Estudios recientes emplean los sistemas de microondas activos y pasivos, junto con datos de la humedad del suelo medidos en campo, para la estimación de la humedad del suelo. Algunos ejemplos de estos trabajos son: Albergel et al 2012 empleando SMOS) con ASCAT; Lacava et al (2012b), utilizando SMOS, AMSR y ASCAT; Brocca et al (2011b), utilizando los sensores ASCAT y AMSR-E y Santi et al (2018) utilizando SMAP, AMSR2 y SENTINEL-1 con el modelo SWBM-GA (Brocca et al, 2008 o Petropoulus et al, (2009) con aplicaciones de SAR para modelos de transferencia suelo-vegetaciónatmosfera (SVAT).…”
Section: Estimaciones Por Teledetección De La Humedad Del Suelounclassified
“…Frecuentemente, en esos trabajos se producen diferencias sistemáticas entre los datos derivados por detección remota y las observaciones in situ, a pesar de que la dinámica temporal sea muy similar. Para solucionar este problema, se han desarrollado varias técnicas de comparación (matching) de la variabilidad de los datos de satélite con la obtenida in situ como la corrección por regresión lineal (Jackson et al, 2010;Brocca et al, 2011b) y mediante funciones de densidad acumulada (CDF matching) (Reichle y Koster 2004;Drusch et al 2005;Lacava et al 2012aLacava et al , 2012b. En este sentido, los trabajos de Lacava et al, (2010Lacava et al, ( , 2012a tienen particular interés, ya que en ellos se emplean, junto con datos in situ y datos del producto de humedad del suelo SMOS, datos modelados con el SWBM-GA (Brocca et al, 2008).…”
Section: La Misión Smos Para La Estimación De La Humedad Superficial unclassified
See 1 more Smart Citation